Buniyamin Engineering Sdn. Bhd.:- Investment Decision Between Joint-Venture in Proton City Project and Privatization of System Service Provider (SSP) - Nik Mahmood, Nik Mohamed Suhaimi (1998)
The Buniyamin Engineering Sdn. Bhd. was incorporated on the ih May 1994. The company was established as construction and civil engineering contractor. Zean Tech Sdn. Bhd. was the associated company created as domain company to undertake new venture especially in IT and telecommunication services. Since the beginning of operation, Buniyamin had been involved in various small to medium size projects costing RM 1 0,000.00 to RM 1,OOO,OOO.OO. Since Buniyamin were in the starting stage of development, the company size were quite small. As the Managing Director of the company, Nik was running the company with the help of two other directors, Mr. Loo and Mr. Ah Heng. Buniyamin received first proposal from Takenaka Corporation to join-venture for development of Proton City. The second proposal came from Ericsson Communication Sdn. Bhd. to privatize its maintenance and services department. In evaluating the two proposals, he did not seek any assistance from any body, using his knowledge learned in his MBA course and tried to apply to the real situation. In analyzing the proposals, several methods were used in analyzing the feasibility of the proposals; they are accounting rate of return (ARR), pay back period, decision tree, standard deviation, risk adjustment discount rate and the financial modeling. From the above method, Nik emphasized the analysis of using decision tree method for the evaluation of the joint venture between Takenaka Corporation and Buniyamin Engineering Sdn. Bhd. for the development of package A3 and A4 of Proton City in Tanjung Malim, Perak. While for the investment analysis of privatization of system service provider (SSP) by Ericsson to Zean Tech Sdn. Bhd., Nik used the financial modeling and simulation of the cash now and return by using the Excel spreadsheet. As conclusion, the proposal for the joint -venture between Takenaka and Buniyamin for the development of Proton City was feasible and gave high returns and needed only a small initial capital investment. The privatization proposal by Ericsson was much risky and needed high initial investment and gain little return which could not cover the operation cost of the Zean Tech Sdn. Bhd., as the result the proposal was not feasible and canceled. Both evaluation techniques were the tool that was used by the Buniyamin and Zean Tech Sdn. Bhd. in evaluating the proposals of investment and facilitate the decision making by management of both companies.